Respuesta :

[tex]\sqrt{b+3}=a[/tex]

b = (a - 3)²

Our aim is to get a to be alone

1) First we get rid of what's in the brackets. So we subtracts each side by 3. Of course, the opposite of subtracting is adding:

b+3 = a²

2) Now we get rid of the squared in a. Opposite of squaring is square rooting.

[tex]\sqrt{b+3} =a[/tex]

3) There we have it. a is now by itself. We can test if we're right by substituting.

Lets make a=2

b=(a-3)²

b= (2-3)²

b= 1

NOW:

[tex]\sqrt{b+3} =a[/tex]

[tex]\sqrt{1+3} =2[/tex]

ACCESS MORE